A glimpse of the connection between PPARγ and macrophage - Yu, Lexiang; Gao, Yuen; Aaron, Nicole; Qiang, Li (Frontiers in Pharmacology, 2023)
Nuclear receptors are ligand-regulated transcription factors that regulate vast cellular activities and serve as an important class of drug targets. Among them, peroxisome proliferator-activated receptors (PPARs) are members of the nuclear receptor family and have been extensively studied for their roles in metabolism, differentiation, development, and cancer, among others. Recently, there has been considerable interest in understanding and defining the function of PPARs and their agonists in regulating innate and adaptive immune responses and their pharmacological potential in combating chronic inflammatory diseases. In this review, we focus on emerging evidence for the potential role of PPARγ in macrophage biology, which is the prior innate immune executive in metabolic and tissue homeostasis. We also discuss the role of PPARγ as a regulator of macrophage function in inflammatory diseases. Lastly, we discuss the possible application of PPARγ antagonists in metabolic pathologies.